Community-acquired Methicillin-resistant Staphylococcus Aureus In A Malaysian Tertiary Centre - Zetti Zainol Rashid; Norazlah Bahari; Amizah Othman; Roslinda Jaafar; Idimaz Jabbari; Anita Sulong; Rohaidah Hashim; Norazah Ahmad; Nurul Azmawati Mohamed @ Abd Aziz (BioMed Central, 2024)
Non-Indexed Publication